Translational and Clinical Relevance of PDX‐Derived Organoid Models in Oncology Drug Discovery and Development. Issue 7 (5th July 2022) - Kumari, Rajendra; Xu, Xiaoxi; Li, Henry Qi‐Xang
Abstract: Patient‐derived cancer disease models conserve many key features of the original human cancers, potentially allowing higher predictive power than traditional cell line models. Accordingly, in vivo patient‐derived xenografts (PDX) are frequently utilized in preclinical and translational oncology studies as patient surrogates for population‐based screens ("mouse clinical trials"), for which large PDX biobanks have been generated over the last decade from various cancer types. In vitro patient‐derived organoids (PDO) have recently emerged as a disruptive technology, enabling early "patient in a dish" clinical trials. Like PDX, PDOs retain the histology/genomics of the original tumor and are highly predictive of the clinical response. Organoids derived from adult stem cells (ASC) in patient tissue can function as mini‐organs. They have greater advantages over other 3D in vitro systems, making them highly predictive, reliable, and consistent in vitro models. Large biobanks enable the adoption of organoids in early drug screening and patient selection. PDX biobanks, as a source of human material, have been used to create 3D in vitro screens, but with limitations. However, creating organoids from the ASCs residing in PDXs has been successfully used as a rapid and cost‐effective way to enable higher throughput in vitro screens and generate matched in vitro/in vivo model pairs that retain genomic, histopathological, and pharmacology profiles. This overview summarizes the generation of matched in vitro/in vivo models from patient material, the advantages over other systems, and the applications to drug discovery. © 2022 Wiley Periodicals LLC.